1994
DOI: 10.1093/infdis/169.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Transmission of Mumps in a Highly Vaccinated Population: Assessment of Primary Vaccine Failure and Waning Vaccine-Induced Immunity

Abstract: From January to July 1991, an outbreak of mumps occurred in Maury County, Tennessee. At the primarily affected high school, where 98% of students and all but 1 student with mumps had been vaccinated before the outbreak, 68 mumps cases occurred among 1116 students (attack rate, 6.1%). Students vaccinated before 1988 (the first year mumps vaccination was required for school attendance in Tennessee) may have been at greater risk of mumps than those vaccinated later (65[6.1%] of 1001 vs. 2[2.2%] of 89; risk ratio,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(87 citation statements)
references
References 18 publications
1
84
0
2
Order By: Relevance
“…Failure of the mumps vaccine has been attributed to primary vaccine failure [24]. Sero-conversion rates following mumps vaccination, estimated by modelling ESEN sero-prevalence data, varied in the different countries [12].…”
Section: Discussionmentioning
confidence: 99%
“…Failure of the mumps vaccine has been attributed to primary vaccine failure [24]. Sero-conversion rates following mumps vaccination, estimated by modelling ESEN sero-prevalence data, varied in the different countries [12].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of sporadic mumps outbreaks is a wellknown phenomenon, even in populations with high vaccine coverage (Wharton et al, 1988 ;Hersh et al, 1991 ;Briss et al, 1994 ;Ku$ nkel et al, 1994Ku$ nkel et al, , 1995Germann et al, 1996 ;Stro$ hle et al, 1996 ;Afzal et al, 1997 b). In the epidemics in Switzerland in 1992and in Portugal in 1996, the population was vaccinated with a heterologous genotype (Ku$ nkel et al, 1994 ;Stro$ hle et al, 1996 ;Afzal et al, 1997 b).…”
Section: Introductionmentioning
confidence: 99%
“…27 In previously reported studies crowded educational settings such as schools, universities, and camps, have played an important role in transmission of mumps. 5,[28][29][30][31][32][33] No evidence has suggested that other factors such as handling changes and vaccine lots were risk factors for vaccine failure.…”
Section: Discussionmentioning
confidence: 99%